2020
DOI: 10.1002/jcp.29810
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative potential of Wharton's jelly‐derived mesenchymal stem cells: A new horizon of stem cell therapy

Abstract: Umbilical cord Wharton's jelly‐derived mesenchymal stem cells (WJ‐MSCs) have recently gained considerable attention in the field of regenerative medicine. Their high proliferation rate, differentiation ability into various cell lineages, easy collection procedure, immuno‐privileged status, nontumorigenic properties along with minor ethical issues make them an ideal approach for tissue repair. Besides, the number of WJ‐MSCs in the umbilical cord samples is high as compared to other sources. Because of these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 114 publications
0
27
0
2
Order By: Relevance
“…Finally, we were able to demonstrate that hPL preparations display a unique profile of factors that are actively taken up by WJ-MSC to support efficient cell expansion while preserving their biological and potential therapeutic features. Advanced Therapy Medicinal Products (ATMP) based on WJ-MSC are currently being under intense development as cell therapeutics due to their regenerative characteristics, potent immunomodulatory properties, low risk for carrying somatic mutations, demonstrated effectivity and absence of adverse effects in the clinical setting, making them a promising therapeutic resource for the treatment of several pathologies involving regeneration of tissue injuries in several systems (neural, myocardial, skin, liver, kidney, cartilage, bone, muscle) [ 18 , 19 ]. Production of MSC-based cellular therapies for clinical use requires the standardization of critical methods for isolation, expansion and conservation of WJ-MSC under conditions that comply with standards of good manufacturing practices (GMP), hereby ensuring proper identity, purity, viability, stability and quantity parameters of the cell compound present in the final product.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we were able to demonstrate that hPL preparations display a unique profile of factors that are actively taken up by WJ-MSC to support efficient cell expansion while preserving their biological and potential therapeutic features. Advanced Therapy Medicinal Products (ATMP) based on WJ-MSC are currently being under intense development as cell therapeutics due to their regenerative characteristics, potent immunomodulatory properties, low risk for carrying somatic mutations, demonstrated effectivity and absence of adverse effects in the clinical setting, making them a promising therapeutic resource for the treatment of several pathologies involving regeneration of tissue injuries in several systems (neural, myocardial, skin, liver, kidney, cartilage, bone, muscle) [ 18 , 19 ]. Production of MSC-based cellular therapies for clinical use requires the standardization of critical methods for isolation, expansion and conservation of WJ-MSC under conditions that comply with standards of good manufacturing practices (GMP), hereby ensuring proper identity, purity, viability, stability and quantity parameters of the cell compound present in the final product.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current evidence, MSCs are spindle-shaped and resemble fibroblasts that can be isolated from a variety of sources such as umbilical cord (UC), Wharton’s jelly (WJ), adipose tissue, bone marrow (BM), teeth and menstrual fluid [ 15 , 20 ]. The MSCs originally explained by Friendenstein et al in 1966 as bone forming cells in BM; nevertheless, they are usually named MSCs because they present adult stem cell multipotency [ 21 ].…”
Section: Mesenchymal Stem Cellmentioning
confidence: 99%
“…In order to utilize them in the clinical studies, it is obligatory to culture separated MSCs in vitro. Because of their ease collection procedure, existence in various tissues, differentiation into various cell lineages, and high proliferation rate, MSCs are more applied in stem cell therapy compared to the other stem cell types [ 15 , 16 ]. The results of studies have demonstrated that MSCs can inhibit the proliferation and function of T lymphocytes, decrease the concentrations of tumor necrosis factor α (TNF-α), increase regulatory T (Treg) cells, regulate the expression of inflammatory mediators, and ameliorate bone injury [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, enzymatic-based protocols are commonly used for the isolation of hUCC by using collagenase, hyaluronidase, or other proteases. Differently, explant-based isolation procedures are used because of higher cell yield and preserving cell membrane protein integrity (Abbaszadeh et al, 2020).…”
Section: Human Umbilical Cord Cells (Hucc)mentioning
confidence: 99%